Climate change and carbon markets : a handbook of emission reduction mechanisms - Yamin, Farhana (Earthscan, 2005)
Climate change is an environmental problem of unprecedented complexity, not just in terms of its physical, social, economic and political impacts, but particularly in terms of the range of policy instruments being designed by countries to reduce greenhouse gas emissions. Climate Change and Carbon Markets aims to provide an accessible and practical guide to cutting edge market-based mechanisms which will reduce greenhouse gas emissions. This book is a guide for national and international policy-makers and industry professionals, who need to understand the carbon markets established pursuant to.